Pilot-Scale Test of Water Wash Carbon Dioxide Absorption System for Purifying Landfill Gas at Jones Island Wastewater Reclamation Facility - (:unkn) unknown (My University, 2019)
Biogas, a product of the digestion of organic material, consists primarily of methane and carbon dioxide. By purifying raw biogas, or removing the carbon dioxide, it can be upgraded to biomethane, which can be used to generate heat and electricity or as a substitute for natural gas. An effective method of biogas purification is the water wash process, which consists of an absorption column in which a stream of biogas runs counter-current to a stream of water. The carbon dioxide dissolves in the water, increasing the methane concentration of the gas. A pilot scale system was operated at Jones Island Wastewater Reclamation Facility in Milwaukee Wisconsin to evaluate the effectiveness of this process by treating landfill gas. The effects of water flow, gas flow, and the gas/water ratio on the water wash system’s efficiency were examined. The system operated best at low gas flow rates, while determining an ideal water flow rate or gas/water ratio proved difficult due to the low water supply pressure.
Keywords: Biogas; Landfill gas purification; Water wash absorption